El debate intracatólico sobre la muerte encefálica estado actual y posibilidades para el desarrollo doctrinal (2021)
This article expounds the debate within the Roman Catholic Church regarding the acceptability of whole-brain death as a valid criterion to determine human death. After reviewing the most dominant stances among catholic scholars on brain death, this article analyses their compatibility with the doctrine about brain death in the 2000’s speech of John Paul II on the matter in order to determine whether the doctrine requires a review, as some scholars argue. After confirming that this debate is really open, since the arguments support both sides of the debate, the article argues that it is necessary to develop a deeper understanding of what means to be a living organism. At the same time, it argues that generally, a whole-brain death provides the necessary moral certainty to legitimately proceed to organ harvesting for transplantation. Nevertheless, there should be room in legislations for conscientious objection regarding the application of the neurological criterion.